Pengembangan Flipbook Materi Konsep Dasar Sustainable Tourism di Universitas Pendidikan Ganesha - Ketut Wahyu Aditya Putra; Luh Masdarini; Ni Made Suriani (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
This study aims to develop and determine the feasibility of a flipbook learning media on the basic concepts of sustainable tourism. The research adopted a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). The subjects consisted of two material experts, two instructional design experts, and two media experts from Ganesha University of Education. Data were collected using validation questionnaires with a 4-point Likert scale and analyzed using quantitative descriptive percentage techniques. The results showed that: (1) the development followed the 4D stages systematically; (2) the flipbook was declared highly feasible with an average percentage of 98% from material experts (very feasible), 95% from instructional design experts (very feasible), and 94% from media experts (very feasible). Thus, the flipbook learning media on the basic concepts of sustainable tourism is valid and suitable for use in the learning process at the Family Welfare Education Study Program, Ganesha University of Education.